Influence of Poly (Ethylene Glycol) 20,000 Concentration on Atomization and Deposition Characteristics of Nozzle - Yuxuan Jiao (MDPI AG, 2021)
The addition of surfactants to pesticide spray applications is an important method to improve the spray atomization and the coverage of droplets on the target. The effects of different types of surfactants on spraying have been extensively studied, but there have been few studies on the commonly used surfactant polyethylene glycol so far. This article compares the effect of polyethylene glycol 20,000 on the atomization and deposition characteristics by measuring the droplet size and the deposition on the polyethylene collection line when spraying different concentrations of polyethylene glycol 20,000 solution. The results show that the volume medium diameter DV0.5 of spraying different concentrations of polyethylene glycol 20,000 solution is larger than that of clear water, and that as the concentration increases, the volume medium diameter DV0.5 gradually increases but ΦVol < 150 μm decreases. Spraying different concentrations of polyethylene glycol 20,000 solution at a horizontal distance of 2–7 m from the nozzle and at a distance of 0.1–0.2 m from the bottom of the floor, the depositions are all less than that of clear water, and as the concentration increases, the deposition becomes smaller. This article can provide theoretical support for the use and concentration ratio of polyethylene glycol 20,000 in field application.